MANAJEMEN FATIGUE UNTUK MENCEGAH MICROSLEEP PADA DRIVER SARANA: FATIGUE MANAGEMENT TO PREVENT MICROSLEEP IN FACILITIES DRIVERS - S. Duna, Benny Irawan; Iashania, Yunida; Mare Apui Ganang, Nuansa (JURNAL TEKNIK PERTAMBANGAN, 2023)
Abstrak Fatigue is a physical and mental state that results in a decrease in work power and reduced body resistance to work safely and effectively. This research was conducted at PT. XX in July 2017 where the bus driver hit a water truck, the fatigue factor caused the incident. The research method used is descriptive quantitative research and interview results. This study aims to provide an overview of potential levels of fatigue and efforts to prevent accidents due to fatigue so as to provide insights and input to prevent mine accidents due to fatigue. The importance of the company's role in creating a Mining Work Safety system apart from the individual's role in terms of rest time management. Re-socializing the implementation of company regulations in the form of Job Safety Analysis (JSA) and Standard Operational Procedure (SOP), ensuring Fatigue Management System and implementation of Fatigue tests for all work partners on an ongoing basis are expected to be efforts to prevent or minimize potential similar mining accidents are repeated. Keywords: Fatigue, Driver, Mine